Pemanfaatan Media Bahan Alam dalam Kegiatan Kolase untuk Mengembangkan Kemampuan Imajinasi Anak Usia Dini di TK PKK Melati Kabupaten Probolinggo - Saiful Hasan; Ahmad Zainullah; Ivone Hafidlatil Kiromi (Universitas Islam Lamongan, 2026)
Motivated by the importance of developing children's imagination through exploratory activities, this study examined the use of natural materials—such as leaves, seeds, twigs, stones, and wood—as learning media to enhance the imagination skills of early childhood students at TK PKK Melati, Probolinggo Regency, to foster meaningful and contextual learning experiences. This qualitative descriptive study, supported by quantitative data, involved 15 children aged 5–6 years and one classroom teacher to analyze their learning experience and development. Data were gathered through observation, interviews, and documentation. Qualitative analysis followed the Miles, Huberman, and Saldaña model, including data reduction, data display, and conclusion drawing, while quantitative data were evaluated using percentage-based on four developmental categories: “Not Yet Developed” (BB), “Beginning to Develop” (MB), “Developing as Expected” (BSH), and “Very Well Developed” (BSB). The findings revealed that the use of natural materials successfully enhanced student's participation, creativity, and imaginative abilities. Before the learning activities, 73% of the children (11 out of 15) fell into the 'Not Yet Developed' (BB; 3 children) and 'Beginning to Develop' (MB; 8 children) categories, whereas 27% (4 children) were in the 'Developing as Expected' (BSH) category. Following the collage learning activity, 87% of the children reached the 'Very Well Developed' (BSB; 8 children) and 'Developing as Expected' (BSH; 5 children) categories, and none remained in the 'Not Yet Developed' (BB) category. It is show that natural materials are effective in developing imagination, demonstrated by improvements in ideation, creative material integration, artistic diversity, and confidence in presenting work.